(untitled) (Revista de Ciências Agroveterinárias, 2019)
Honey is a product naturally produced by bees and, due to its composition, it has a characteristic flavor and high nutritional value. Its use is known since antiquity and each day it conquers new consumer markets. The demand for quality products available for human expenditure reflects the need for better supervision during the production process. The goal for this research was to evaluate the physio-chemical and microbiological quality of 22 honey samples with inspection and informal commerce registers in different cities in Paraná, Rio Grande do Sul and Santa Catarina. The following parameters were analyzed: total acidity, pH, insoluble solids, diastase activity, hydroxymethylfurfural, Fiehe, Lugol, Lund reactions, and the presence of mold and yeast. As to the physical-chemical characteristics, 54.54% of the samples presented some shortcoming with the parameters established by the legislation. Although the law doesn’t demand microbiological analyses, 45.45% of the samples presented mold and yeast.